Role of Combined Multivitamin and Iron Therapy against Vitamin A in the treatment of Iron-Deficient Anemic Women (Medical Forum Monthly, 2023)
Objective: To determine if such medication affected blood vitamin A levels and whether it enhanced patients' general health.Study Design: Analytical / Descriptive StudyPlace and Duration of Study: This study was conducted at the Pharmacology, Islamic International Medical College Rawalpindi from January 2022 to January 2023.Materials and Methods: Total 100 patients with iron deficient anaemia were included in the trial from the Department of Pharmacology, Islamic International Medical College Rawalpindi. All participants received daily multivitamins and doses of an iron supplement for a period of 12 weeks. The dosage was suggested taking into consideration the patient's age, weight, and hemoglobin levels. All of the dietary supplements used in the research are fortified with iron, calcium, zinc, and vitamins A, B, C, D, and E. Before and after the therapy period, their haemoglobin, serum ferritin, and serum vitamin A levels were evaluated. The body's iron reserves were evaluated using the serum ferritin level. The blood vitamin A level was observed to determine the impact of the multivitamin and iron supplement on the amount of this vital vitamin in the body.Results: According to the research, serum ferritin and hemoglobin levels notably rose in comparison to baseline values throughout the therapy period (p 0.001). Additionally, the medication significantly raised the amount of vitamin A in the blood (p 0.001).Conclusion: This research suggest that multivitamins and iron therapy administered together may raise vitamin A levels and, as a consequence, reduce the risk of vitamin A deficiency in anemic women who are deficient in iron. The increased levels of serum ferritin and hemoglobin also demonstrate how the treatment enhanced the patients' overall health.